Unequal Childhoods: Young Children's Lives in Poor Countries - Penn, Helen (Contesting Early Childhood, 2005)
An expert in her field, Helen Penn discusses the inequalities between and within countries of childhood poverty and how this poverty is recognized and defined through the following case-studies: Kazakhstan - once part of the Soviet Union Swaziland - a country in Southern Africa devastated by HIV and AIDS Himalayan India Brazil - one of the world's most unequal countries. These four case studies illustrate the diversity and complexity of the responses to the attempts to globalise childhood and highlight the need to address the inequalities of childhood experience. Helen Penn is Professor of Early Childhood, University of East London. 1. Global inequalities 2. Interpreting Poverty 3. Understanding Early Childhood 4. Lending a Helping Hand 5. Kazakhstan 6. Swaziland 7. India 8. Brazil 9. The Ethics of Intervention 'Penn has visited the places she describes, so she is able to give first-hand accounts ... Penn concludes these shocking snapshots of an international disgrace with positive suggestions about what can be done ... It is a powerful story well told.' - Times Educational Supplement 'Penn ... gives an insight into the practices of governments and international non-governmental organisations. By summarising discourses on these key theories it is possible for readers from all disciplines to understand the key issues being addressed. Further, the language used throughout the book makes it easily readable and understandable.' - Children's Geographies